CCR5 receptor antagonists block metastasis to bone of v-Src oncogene-transformed metastatic prostate cancer cell lines - Sicoli, Daniela; Jiao, Xuanmao; Ju, Xiaoming; Velasco-Velazquez, Marco; Ertel, Adam; Addya, Sankar; Li, Zhiping; Andò, Sebastiano; Fatatis, Alessandro; Paudyal, Bishnuhari; Cristofanilli, Massimo; Thakur, Mathew L; et al. (Cancer research (Chicago, Ill.), 2014)
Src family kinases (SFK) integrate signal transduction for multiple receptors, regulating cellular proliferation, invasion, and metastasis in human cancer. Although Src is rarely mutated in human prostate cancer, SFK activity is increased in the majority of human prostate cancers. To determine the molecular mechanisms governing prostate cancer bone metastasis, FVB murine prostate epithelium was transduced with oncogenic v-Src. The prostate cancer cell lines metastasized in FVB mice to brain and bone. Gene expression profiling of the tumors identified activation of a CCR5 signaling module when the prostate epithelial cell lines were grown in vivo versus tissue cultures. The whole body, bone, and brain metastatic prostate cancer burden was reduced by oral CCR5 antagonist. Clinical trials of CCR5 inhibitors may warrant consideration in patients with CCR5 activation in their tumors.